2015
DOI: 10.1002/jcb.24985
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3Metabolites Enhance the NLRP3-Dependent Secretion of IL-1β From Human THP-1 Monocytic Cells

Abstract: Vitamin D3 has emerged as an important regulator of the immune system. With metabolic enzymes for vitamin D3 activation and vitamin D receptors (VDR) now identified in a variety of immune cells, the active vitamin D3 metabolite 1,25(OH)2D3, is thought to possess immunomodulatory properties. We examined whether 1,25(OH)2D3 might also enhance the NLRP3-dependent release of mature IL-1β from macrophages. PMA-differentiated THP-1 cells were stimulated with vitamin D3 metabolites and assessed for CYP27, CYP24, NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…promotes innate immunity by increasing chemotactic and phagocytic activity and production of the antimicrobial peptide cathelicidin (32). Vitamin D metabolites can also enhance interleukin-1 (IL-1) secretion through activation of inflammasomes (33). However, the present data provided further evidence for the therapeutic benefits of 25-OHD3 on COPD and periodontitis through its anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 65%
“…promotes innate immunity by increasing chemotactic and phagocytic activity and production of the antimicrobial peptide cathelicidin (32). Vitamin D metabolites can also enhance interleukin-1 (IL-1) secretion through activation of inflammasomes (33). However, the present data provided further evidence for the therapeutic benefits of 25-OHD3 on COPD and periodontitis through its anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 65%
“…Further mechanistic research proved that VDR ligand calcitriol exert inhibiting effect on NLRP3 pathway via Nrf2 activation in human corneal epithelial cells and may serves a potential therapy of dry eye which is a common ocular surface problem (Dai et al, 2019). However, the regulatory effect of VDR ligands on NLRP3 signal and immunomodulatory properties was controversial, the study of Tulk et al (2015) Proved that 1,25(OH)2D3, a VDR active ligand, could enhance the NLRP3 activation and the secrection of its downstream proinflammatory effector IL-1β in human THP-1 monocytic cells. Given the results of several previous studies, hence, we hypothesize the existence of a close relationship between VDR and the NLRP3 inflammasome signal and assume that NLRP3 inhibition through VDR activation may induce anti-fibrosis and anti-inflammatory effects in cholestatic liver injury, which may serve as a new mechanism of the liverprotective effect of VDR.…”
Section: Introductionmentioning
confidence: 99%
“…NLRP3 activation has been associated with pathogenesis of AMD and its role has been linked with autophagy (Celkova et al, 2015;Kauppinen et al, 2016). It was reported that both, 1,25(OH)2D and 25(OH)D had increased the release of IL-1α from human monocytes with this effect being dependent on caspase-1 and NLRP3 (Tulk et al, 2015).…”
Section: Susceptibility Genesmentioning
confidence: 98%